Non-conforming elements in nek5000: Pressure preconditioning and parallel performance - Peplinski, A.; Offermans, N.; Fischer, P. F.; Schlatter, Philipp (Lecture Notes in Computational Science and Engineering, 2020)
Adaptive mesh refinement (AMR) is an important component of modern numerical solvers, as it allows to control the computational error during the simulation, increasing the reliability of the numerical modelling and giving the possibility to study a broad range of different phenomena even without knowing the physics a priori. In this work we present selected aspects of the implementation and parallel performance of a new h-type AMR framework developed for the high-order CFD solver Nek5000; the development was done within the ExaFLOW EU project. We utilise in this case the natural domain decomposition inherent to the spectral element method (SEM), which constitutes the main source of parallelism and provides meshing flexibility that can be exploited in AMR. We use standard libraries for parallel mesh management (p4est) and partitioning (ParMetis) and focus on developing efficient preconditioners for the pressure problem solved on non-conforming meshes. Two different approaches are considered: an additive overlapping Schwarz and a hybrid Schwarz-multigrid method. The strong scaling is shown on the example of the simulation of the turbulent flow around a NACA4412 wing section at Re = 200, 000.
CRIS-Team Scopus Importer:2023-03-21